Water-Cooling-Based Approach for PV System Performance Enhancement towards UAE Future Energy Efficiency Policies - Hossin, Khaled; Attia, Hussain (International Journal of Energy Economics and Policy, 2024)
United Arab Emirates (UAE) has implemented the UAE Energy Strategy 2050, targeting a 50% increase in renewable energy’s contribution by 2050. Steps to achieve this strategy include accelerating efficient consumption of energy and focusing on research and development for sustainable energy solutions. This research aims to investigate the potential improvement in the performance of PV systems as a result of panel’s water-cooling under the UAE climatic conditions. In this work, a PV system consists of two identical 100-W PV panels and an automated water cooling arrangement was built. To assess the effectiveness of the cooling method used, one PV panel was subjected to water cooling, while the other remained uncooled in order to be taken as a benchmark. The experiments took place over a typical summer day during the period between 8:00 am and 5:00 pm. The proposed cooling strategy was repeatedly applied every half an hour to investigate the temperature reduction behavior at different times of the day. The experimental results demonstrated that the adopted water approach was able to achieve a temperature drop of up to 14.6 K. The corresponding power output was improved by up to 12% as a result of the PV panel cooling.